Telesna aktivnost, antioksidanti in oksidativni stres - Meden, Vesna Mila; Rauter, Vesna (University of Maribor Press, 2022)
Physical Activity, Antioxidants and Oxidative Stress. Reactive species are released during physical activity; the extent of their occurrence is related to the characteristics of physical exercise. The release of reactive species that exceeds the ability of antioxidant defense causes oxidative stress. Under physiological conditions, the balance between the release rate of reactive species and antioxidant defense is shifted slightly to the side of oxidative processes. This balance is disrupted by two extremes of physical activity: acute, high-intensity physical activity and physical inactivity. The challenge of evaluating the state of oxidative stress in the body is extremely relevant. The results of our own research in the field of antioxidants point to the need for an interdisciplinary approach to such research. The results of the research are compared with the findings of researchers in the world, so the presented knowledge is extremely current. In order to stimulate curiosity and enthusiasm for research, the content especially addresses the population of young people, especially students. Education on the key role of physical activity in maintaining homeostasis and consequently health and longevity should be part of the content of basic subjects in all study programs of universities and higher education institutions.